Cold-atom systems and the scaling limit - Tomio, L. [UNESP] (Springer Wien, 2008)
With perspective to applications of cold-atom systems, some aspects of few-body physics at very low energies will be reviewed. By exploring the possibilities of varying the two-body interaction via the Feshbach resonance mechanism, some recent results are reported for condensed systems in optical lattices.